Being a sociable designer: reimagining the role of designers in social innovation. Issue 1 (2nd January 2022) - Tjahja, Cyril; Yee, Joyce
ABSTRACT: The democratisation of the creative process in design and social innovation has brought the position of the designer into question. Therefore, a shift is necessary from the traditional role-based approach towards one that is value-based. This paper introduces the sociable designer, who is driven by being social, rather than doing social. Based on insights from field work conducted in Hong Kong, Bangkok and Kuala Lumpur, this reorientation highlights the value of design in supporting the reconfiguration of social relationships by thinking of design as a socially-embedded practice.